<em>Answer: Reflection=simply flipping an object across a line without changing its size or shape. While Translation just slide a figure in any direction without changing its size, shape or orientation.</em>
<em />
<em>Hopes that helps have a blessing day/night :)</em>
<em />
Answer:
![34+24.5h](https://tex.z-dn.net/?f=34%2B24.5h)
Step-by-step explanation:
![8.5(4+3h)-h\\\\=8.5(4)+8.5(3h)-h\\\\=34+25.5h-h\\\\=34+24.5h](https://tex.z-dn.net/?f=8.5%284%2B3h%29-h%5C%5C%5C%5C%3D8.5%284%29%2B8.5%283h%29-h%5C%5C%5C%5C%3D34%2B25.5h-h%5C%5C%5C%5C%3D34%2B24.5h)
Answer: see proof below
<u>Step-by-step explanation:</u>
Given: A + B + C = π → C = π - (A + B)
→ sin C = sin(π - (A + B)) cos C = sin(π - (A + B))
→ sin C = sin (A + B) cos C = - cos(A + B)
Use the following Sum to Product Identity:
sin A + sin B = 2 cos[(A + B)/2] · sin [(A - B)/2]
cos A + cos B = 2 cos[(A + B)/2] · cos [(A - B)/2]
Use the following Double Angle Identity:
sin 2A = 2 sin A · cos A
<u>Proof LHS → RHS</u>
LHS: (sin 2A + sin 2B) + sin 2C
![\text{Sum to Product:}\qquad 2\sin\bigg(\dfrac{2A+2B}{2}\bigg)\cdot \cos \bigg(\dfrac{2A - 2B}{2}\bigg)-\sin 2C](https://tex.z-dn.net/?f=%5Ctext%7BSum%20to%20Product%3A%7D%5Cqquad%202%5Csin%5Cbigg%28%5Cdfrac%7B2A%2B2B%7D%7B2%7D%5Cbigg%29%5Ccdot%20%5Ccos%20%5Cbigg%28%5Cdfrac%7B2A%20-%202B%7D%7B2%7D%5Cbigg%29-%5Csin%202C)
![\text{Double Angle:}\qquad 2\sin\bigg(\dfrac{2A+2B}{2}\bigg)\cdot \cos \bigg(\dfrac{2A - 2B}{2}\bigg)-2\sin C\cdot \cos C](https://tex.z-dn.net/?f=%5Ctext%7BDouble%20Angle%3A%7D%5Cqquad%202%5Csin%5Cbigg%28%5Cdfrac%7B2A%2B2B%7D%7B2%7D%5Cbigg%29%5Ccdot%20%5Ccos%20%5Cbigg%28%5Cdfrac%7B2A%20-%202B%7D%7B2%7D%5Cbigg%29-2%5Csin%20C%5Ccdot%20%5Ccos%20C)
![\text{Simplify:}\qquad \qquad 2\sin (A + B)\cdot \cos (A - B)-2\sin C\cdot \cos C](https://tex.z-dn.net/?f=%5Ctext%7BSimplify%3A%7D%5Cqquad%20%5Cqquad%202%5Csin%20%28A%20%2B%20B%29%5Ccdot%20%5Ccos%20%28A%20-%20B%29-2%5Csin%20C%5Ccdot%20%5Ccos%20C)
![\text{Given:}\qquad \qquad \quad 2\sin C\cdot \cos (A - B)+2\sin C\cdot \cos (A+B)](https://tex.z-dn.net/?f=%5Ctext%7BGiven%3A%7D%5Cqquad%20%5Cqquad%20%5Cquad%202%5Csin%20C%5Ccdot%20%5Ccos%20%28A%20-%20B%29%2B2%5Csin%20C%5Ccdot%20%5Ccos%20%28A%2BB%29)
![\text{Factor:}\qquad \qquad \qquad 2\sin C\cdot [\cos (A-B)+\cos (A+B)]](https://tex.z-dn.net/?f=%5Ctext%7BFactor%3A%7D%5Cqquad%20%5Cqquad%20%5Cqquad%202%5Csin%20C%5Ccdot%20%5B%5Ccos%20%28A-B%29%2B%5Ccos%20%28A%2BB%29%5D)
![\text{Sum to Product:}\qquad 2\sin C\cdot 2\cos A\cdot \cos B](https://tex.z-dn.net/?f=%5Ctext%7BSum%20to%20Product%3A%7D%5Cqquad%202%5Csin%20C%5Ccdot%202%5Ccos%20A%5Ccdot%20%5Ccos%20B)
![\text{Simplify:}\qquad \qquad 4\cos A\cdot \cos B \cdot \sin C](https://tex.z-dn.net/?f=%5Ctext%7BSimplify%3A%7D%5Cqquad%20%5Cqquad%204%5Ccos%20A%5Ccdot%20%5Ccos%20B%20%5Ccdot%20%5Csin%20C)
LHS = RHS: 4 cos A · cos B · sin C = 4 cos A · cos B · sin C ![\checkmark](https://tex.z-dn.net/?f=%5Ccheckmark)
Answer:
x = -2
Step-by-step explanation:
hope this helps you
The answer is option c- 68°